Sena Technology Inc. / Muhammad Amirul Harish Mohammed Hanafi - Mohammed Hanafi, Muhammad Amirul Harish (2022)
Sena Technology Inc. that is focused in Information Technology and Services have invented in Bluetooth Helmet. This helmet has many abilities and function that useful to rider. However, this product still has weakness and need an improvement .The first problem for this helmet is it has heavy weight. Although this looks like a small matter, but it can cause the rider feels uncomfortable and muscle pain. Then, the helmet also has a limited battery capacity. It will make the helmet can’t function well after the battery drained. There were several solutions that have found to help to improve the helmet. One of the solutions is use graphene material instead of fiber metal to produce the helmet. It can help to reduce the weight of helmet. Besides that, the additional of solar cell can help the helmet to generate and store more energy power.